A processing method for improving glass melting efficiency by plasma pretreating powder
Patent Information
- Application Number
- CN202611382251.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-08
- Publication Date
- 2026-10-27
AI Technical Summary
现有的玻璃熔制工艺中,配合料中的含硅原料粉体直接入窑熔制时,石英砂颗粒表面的硅氧网络结构完整且致密,熔制过程中热量需要从颗粒表面逐步向内部传递,同时助熔剂组分与石英砂的反应也首先发生在颗粒表面,随着表层石英砂逐渐溶解,内部的硅氧网络才能逐步暴露并与助熔剂接触,这种逐层反应的方式使石英砂颗粒的完全熔融需要较长的保温时间和较高的熔制温度,整个熔制过程的效率受到石英砂颗粒熔融速度的限制
1、通过双频复合射频电源的协同作用实现了含硅原料粉体从表层到体相的梯度活化。低频射频源产生的较高能量离子能够在颗粒表层下方产生晶格畸变和结构疏松区域,高频射频源产生的高密度活性粒子使颗粒最表层的硅氧键断裂并形成无序结构,二者的配合使粉体颗粒从表面到内部形成活化程度递减的梯度分布状态,为后续助熔剂组分的锚定和渗透提供了结构基础。
Smart Images

Figure CN122977674A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of glass manufacturing technology, specifically to a processing method for improving glass melting efficiency using plasma pretreatment powder. Background Technology
[0002] Glass melting is the core step in the glass production process. Its basic principle is to heat and melt batch materials such as quartz sand, soda ash, and limestone at high temperature, so that solid-phase reaction and liquid-phase formation occur between the components, and finally a uniform and clear glass melt is obtained. In existing glass melting processes, when silicon-containing raw material powder in the batch is directly fed into the kiln for melting, the silicon-oxygen network structure on the surface of the quartz sand particles is complete and dense. During the melting process, heat needs to be transferred from the particle surface to the interior gradually. At the same time, the reaction between the flux components and the quartz sand also occurs first on the particle surface. As the surface layer of quartz sand gradually dissolves, the internal silicon-oxygen network can be gradually exposed and come into contact with the flux. This layer-by-layer reaction means that the complete melting of the quartz sand particles requires a long holding time and a high melting temperature. The efficiency of the entire melting process is limited by the melting rate of the quartz sand particles. Summary of the Invention
[0003] To address the shortcomings of existing technologies, this invention provides a processing method for improving glass melting efficiency by plasma pretreatment of powder. Through dual-frequency plasma gradient activation, flux component gradient anchoring, and synergistic injection of plasma gas flow during the melting process, the deagglomeration process of the silicon-oxygen network of silicon-containing raw material powder is pre-enhanced and continues throughout the entire melting stage. This significantly reduces the energy consumption and time cost of the melting process while ensuring the uniformity and clarity of the molten glass.
[0004] To achieve the above objectives, the present invention provides the following technical solution: a processing method for improving glass melting efficiency using plasma pretreated powder, comprising the following steps: Step 1: Place the silicon-containing raw material powder in the glass batch into a rotary plasma reactor. Under vacuum or inert atmosphere, apply a dual-frequency composite radio frequency power supply. The dual-frequency composite radio frequency power supply includes a first radio frequency source and a second radio frequency source. The frequency of the first radio frequency source is 2 to 10 MHz, and the frequency of the second radio frequency source is 40 to 100 MHz. The two radio frequency sources work simultaneously to obtain a bulk phase surface interface synergistically activated powder. Step 2: The bulk-to-interface synergistic activated powder obtained in Step 1 is mixed with a liquid flux precursor and spray-coated. The liquid flux precursor is an organic solution of alkali metal alkoxide or alkaline earth metal alkoxide. During the coating process, the liquid flux precursor is atomized, and the atomized droplets are deposited on the surface of the bulk-to-interface synergistic activated powder. Then, vacuum drying is performed to obtain active component gradient anchored powder. Step 3: The active component gradient anchoring powder obtained in Step 2 is mixed with the remaining raw material powder in the glass batch and then fed into the glass melting furnace for melting. At the same time, during the entire melting process or at least the early stage of melting, plasma activation gas flow is continuously or intermittently injected into the bottom of the molten pool or the batch layer of the glass melting furnace. The plasma activation gas flow is a gas flow containing long-lived active species generated by ionizing the working gas through an external plasma generator, resulting in a uniform and clear glass melt.
[0005] Preferably, in step one, the particle size of the silicon-containing raw material powder is 10-500 μm, and the particle size distribution span (D90-D10) / D50 ≤ 2.0; the absolute pressure of the vacuum or inert atmosphere is 1-100 Pa, and the inert gas used is argon or helium; the inner wall of the rotary plasma reactor is equipped with a baffle plate, and the rotation speed is 1-20 rpm; the power of the first radio frequency source is 50-300 W, and the power of the second radio frequency source is 100-600 W.
[0006] Preferably, in step one, the processing temperature is room temperature to 300°C, and the processing time is 5 to 60 minutes; the dual-frequency composite radio frequency power supply makes the ion energy distribution in the plasma exhibit a double-peak characteristic, wherein the energy of the low-energy ion peak is 1 to 5 eV, and the energy of the high-energy ion peak is 10 to 30 eV.
[0007] Preferably, in step two, the mass ratio of the bulk phase interface synergistic activated powder to the liquid flux precursor is 1:0.1-0.5; the alkali metal alkoxide is at least one of sodium methoxide, sodium ethoxide, and potassium isopropoxide; the alkaline earth metal alkoxide is at least one of magnesium ethoxide and calcium isopropoxide; the organic solvent is at least one of anhydrous methanol, anhydrous ethanol, or isopropanol; and the vacuum drying temperature is 80-180°C, the time is 10-60 minutes, and the absolute pressure is 100-1000 Pa.
[0008] Preferably, in step two, the liquid flux precursor is atomized using an ultrasonic atomizing device, wherein the ultrasonic frequency of the ultrasonic atomizing device is 20–100 kHz and the average diameter of the atomized droplets is 1–50 μm.
[0009] Preferably, in step one, while applying the dual-frequency composite radio frequency power supply, an axial magnetic field is also applied to the silicon-containing raw material powder, and the magnetic field strength is 0.01 to 0.5T.
[0010] Preferably, in step three, the working gas of the plasma activation gas flow is one or more of the following mixed gases: argon, oxygen, hydrogen, and water vapor; the external plasma generator is one of the following: a dielectric barrier discharge generator, a microwave plasma generator, or a radio frequency inductively coupled plasma generator; the long-lived active species include at least one of the following: metastable inert gas atoms, oxygen free radicals, hydrogen free radicals, and OH free radicals; and the injection flow rate of the plasma activation gas flow is 50–1000 mL / min.
[0011] Preferably, in step three, the plasma activation gas flow is injected from the side wall or bottom of the glass melting furnace through a high-temperature resistant corundum tube or a platinum-rhodium alloy tube, with the injection point located 50-300 mm below the surface of the molten pool; the plasma activation gas flow is injected in a pulsed manner, with a pulse width of 1-60 seconds and a pulse interval of 10-300 seconds.
[0012] Preferably, in step three, the melting temperature in the furnace is 1200–1650°C, the heating rate is 5–20°C / minute, and the total melting time is 0.5–3 hours.
[0013] This invention provides a processing method for improving glass melting efficiency using plasma pretreated powder. Compared with existing technologies, it has the following advantages: 1. The synergistic effect of dual-frequency composite radio frequency power supplies enables gradient activation of silicon-containing raw material powder from the surface to the bulk phase. The high-energy ions generated by the low-frequency radio frequency source can create lattice distortion and loosely structured regions below the particle surface, while the high-density active particles generated by the high-frequency radio frequency source cause the silicon-oxygen bonds on the outermost layer of the particles to break and form a disordered structure. The combination of the two results in a gradient distribution of powder particles with decreasing activation levels from the surface to the interior, providing a structural basis for the subsequent anchoring and penetration of flux components.
[0014] 2. The gradient anchoring of fluxing active components in activated powder is achieved through alkoxide solution atomization coating and vacuum drying processes. The micron-sized droplets after atomization can penetrate into the pores of the activated layer on the powder surface. After drying, the alkali metal or alkaline earth metal components generated by the decomposition of alkoxide are not only anchored in the surface pores, but also migrate into the particle interior along the loose structure, forming a concentration gradient distribution from the surface to the interior. Through the gradient anchoring structure, the active components on the surface react with the silicon raw material first during the melting process, and the internal active components continue to diffuse outward to replenish it, ensuring the persistence and uniformity of the fluxing effect, while avoiding the problem of uneven composition caused by directly mixing in a large amount of flux.
[0015] 3. By pulse-injecting plasma activation gas flow from below the molten pool surface during the melting process, active species directly enter the interior of the glass melt to participate in the melting process. Oxygen free radicals promote the release of alkali metal ions from anchoring points into the silicon-oxygen network, while hydrogen free radicals and OH free radicals directly attack silicon-oxygen bonds to reduce the depolymerization activation energy. Metastable inert gas atoms accelerate the mass transfer and diffusion process in the melt through energy transfer. At the same time, rising bubbles stir the melt and carry out tiny bubbles, so that the homogenization and clarification of the melt are completed simultaneously. This improves the melting efficiency while enhancing the uniformity and quality of the glass melt. Attached Figure Description
[0016] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation
[0017] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0018] Please see Figure 1 This invention provides a technical solution: a processing method for improving glass melting efficiency using plasma pretreated powder, comprising the following steps: Step 1: Place the silicon-containing raw material powder in the glass batch into a rotary plasma reactor. Under vacuum or inert atmosphere, apply a dual-frequency composite radio frequency power supply. The dual-frequency composite radio frequency power supply includes a first radio frequency source and a second radio frequency source. The frequency of the first radio frequency source is 2-10MHz, and the frequency of the second radio frequency source is 40-100MHz. The two radio frequency sources work simultaneously to obtain bulk phase interface synergistically activated powder. Step 2: The bulk-to-interface synergistic activated powder obtained in Step 1 is mixed with a liquid flux precursor and spray-coated. The liquid flux precursor is an organic solution of alkali metal alkoxide or alkaline earth metal alkoxide. During the coating process, the liquid flux precursor is atomized, and the atomized droplets are deposited on the surface of the bulk-to-interface synergistic activated powder. Then, vacuum drying is performed to obtain active component gradient anchored powder. Step 3: The active component gradient anchoring powder obtained in Step 2 is mixed with the remaining raw material powder in the glass batch and then sent to the glass melting furnace for melting. At the same time, during the entire melting process or at least the early stage of melting, plasma activation gas flow is continuously or intermittently injected into the bottom of the molten pool or the batch layer of the glass melting furnace. The plasma activation gas flow is a gas flow containing long-lived active species generated by ionizing the working gas through an external plasma generator, resulting in a uniform and clear glass melt.
[0019] In this embodiment, step one utilizes a dual-frequency composite radio frequency power supply to generate plasma. The low-frequency radio frequency source (2-10 MHz) provides high kinetic energy to the ions in the plasma, allowing them to transfer energy to the shallow inner layer of the silicon-containing raw material powder upon impact, creating lattice distortion and locally loose structural regions below the particle surface. The high-frequency radio frequency source (40-100 MHz) provides sufficient energy to the electrons in the plasma to maintain a high-density ionization state. The high-density active particles interact with the outermost layer of the particles, causing the Si-O bonds to break and forming a disordered structure. These two interactions create activation states at different depths from the particle surface to the interior. In step two, an alkoxide solution is atomized and sprayed onto the activated powder surface. The droplets penetrate into the surface activation layer formed in step one. After vacuum drying to remove the organic solvent, the alkoxide decomposes into oxides or carbonates of alkali metals or alkaline earth metals, remaining within the pores of the activation layer. Because a loose structure has been formed on the particle surface in step one, some active components will also penetrate into the particle interior along the loose regions. Ultimately, a distribution state in which the concentration of active components gradually decreases from the surface to the interior is formed. In the subsequent melting process, the active components on the surface react with the silicon raw material first. As the reaction proceeds, the active components inside gradually diffuse outward to replenish the material, so that the fluxing effect continues. In step three, the coated powder is put into the furnace for melting. At the same time, during the melting process, a plasma activation gas flow is introduced into the glass melt from below the liquid surface. After the oxygen free radicals, hydrogen free radicals or metastable gas atoms carried in the gas flow enter the glass melt, the oxygen free radicals help to dissociate alkali metal ions from carbonate or oxide forms and enter the silicon-oxygen network. The hydrogen free radicals and OH free radicals can directly attack the Si-O bonds and break them. The metastable atoms transfer energy to the melt through collisions with melt particles to accelerate ion diffusion. At the same time, the gas flow itself rises from the inside of the melt in the form of bubbles, which drives the melt to generate local flow, making the components mix more evenly. It also carries and merges small bubbles in the melt and discharges them to the liquid surface, thereby shortening the refining time and finally obtaining a glass melt with low bubble content and uniform composition.
[0020] Specifically, in step one, the particle size of the silicon-containing raw material powder is 10–500 μm, and the particle size distribution span (D90-D10) / D50 ≤ 2.0; the absolute pressure of the vacuum or inert atmosphere is 1–100 Pa, and the inert gas used is argon or helium; the inner wall of the rotary plasma reactor is equipped with baffles, and the rotation speed is 1–20 rpm; the power of the first radio frequency source is 50–300 W, and the power of the second radio frequency source is 100–600 W.
[0021] In this embodiment, the particle size of the silicon-containing raw material powder is controlled between 10 and 500 μm, and the particle size distribution span does not exceed 2.0. This is because fine powder with a particle size less than 10 μm is prone to sintering or agglomeration under plasma bombardment, while coarse particles with a particle size greater than 500 μm have too small a specific surface area, resulting in insufficient efficiency of plasma treatment per unit mass of powder. A distribution span exceeding 2.0 means that the difference between coarse and fine particles is too large, and under the same treatment conditions, fine particles may be over-treated while coarse particles are under-treated. The vacuum degree is controlled between 1 and 100 Pa, and argon or helium is introduced because the mean free path of gas molecules is on the order of millimeters under this pressure range, which can maintain a stable gas discharge. At the same time, argon and helium are both inert gases and will not chemically react with the powder, serving only as the working medium of the plasma. The reactor rotates at a speed of 1 to 20 rpm, and a baffle plate is provided on the inner wall. During the rotation, the powder is carried by the baffle plate to a certain position. After reaching a certain height, the material falls to form a waterfall-like curtain. In this curtain state, the powder particles are dispersed in a single layer or thin layer, avoiding the problem that the bottom particles cannot contact the plasma when the powder is piled up, ensuring that all particles can be processed uniformly. The power of the first radio frequency source is set to 50-300W. This low-frequency source mainly determines the ion bombardment energy. When the power is below 50W, the ion kinetic energy is insufficient to penetrate the particle surface and enter the bulk phase. When the power is above 300W, the ion bombardment energy is too high, which may sputter and peel off the particle surface instead of forming a loose structure. The power of the second radio frequency source is set to 100-600W. This high-frequency source mainly determines the plasma density. When the power is below 100W, the discharge is unstable and the concentration of active particles is insufficient. When the power is above 600W, the equipment cost increases significantly and the excessive particle flux will cause the powder temperature to rise rapidly, exceeding the processing temperature range of room temperature to 300℃, resulting in unnecessary sintering or phase transformation of the particles.
[0022] Specifically, in step one, the processing temperature is room temperature to 300℃, and the processing time is 5 to 60 minutes; the dual-frequency composite radio frequency power supply makes the ion energy distribution in the plasma exhibit a double-peak characteristic, in which the energy of the low-energy ion peak is 1 to 5 eV, and the energy of the high-energy ion peak is 10 to 30 eV.
[0023] In this embodiment, the processing temperature is controlled between room temperature and 300°C because temperatures below room temperature require additional cooling equipment, increasing costs and being unnecessary. While temperatures exceeding 300°C can remove moisture and volatile components adsorbed on the surface of silicon-containing raw material powder particles, for silicon-containing raw materials like quartz sand, a crystal transformation or softening at atmospheric pressure requires at least 573°C (β-quartz to α-quartz transformation) or higher. Therefore, temperatures below 300°C are sufficient to ensure the powder maintains its original solid particle morphology during plasma treatment, preventing particle adhesion or sintering. This temperature range also provides a good surface chemical state for effective anchoring of active components during subsequent alkoxide coating. The processing time is controlled between 5 and 60 minutes because less than 5 minutes results in insufficient accumulation of plasma bombardment and activation effects on the powder, preventing the formation of sufficiently deep activation zones on the particle surface and shallow layers. After 60 minutes, the activation effect tends to saturate, and further extending the processing time only reduces production efficiency and increases energy consumption. It is not economically viable to consume high-energy ions. The dual-frequency composite radio frequency power supply makes the ion energy distribution in the plasma exhibit a bimodal characteristic, in which a low-energy ion peak of 1-5 eV and a high-energy ion peak of 10-30 eV coexist. This is because the ions generated by the low-frequency radio frequency source (2-10 MHz) have a larger oscillation amplitude in the radio frequency field and have higher energy when they reach the powder surface, which is responsible for generating the high-energy peak. On the other hand, the ions generated by the high-frequency radio frequency source (40-100 MHz) have a smaller oscillation amplitude due to their higher frequency and have lower energy when they reach the surface, which is responsible for generating the low-energy peak. The two types of ions with different energies act at different depths of the powder. The high-energy ions can penetrate to a position tens to hundreds of nanometers below the particle surface and generate defects in the bulk phase. The low-energy ions are concentrated in the outermost few nanometer range of the particles and are responsible for breaking the surface chemical bonds and amorphization. If there are only high-energy ions and no low-energy ions, the surface layer will be over-bombarded and peel off. If there are only low-energy ions and no high-energy ions, the interior of the bulk phase will not be activated. Only when both coexist can gradient activation from the surface to different depths inside be achieved.
[0024] Specifically, in step two, the mass ratio of the bulk phase surface interface synergistic activation powder to the liquid flux precursor is 1:0.1-0.5; the alkali metal alkoxide is at least one of sodium methoxide, sodium ethoxide, and potassium isopropoxide, the alkaline earth metal alkoxide is at least one of magnesium ethoxide and calcium isopropoxide, and the organic solvent is at least one of anhydrous methanol, anhydrous ethanol, or isopropanol; the vacuum drying temperature is 80-180℃, the time is 10-60 minutes, and the absolute pressure is 100-1000 Pa.
[0025] In this embodiment, the mass ratio of powder to liquid flux precursor is set to 1:0.1 to 1:0.5 because when the ratio is below 0.1, the total amount of precursor is too small to form a continuous coating on the powder surface, and some particle surfaces cannot be anchored with enough active components, resulting in uneven fluxing effect. When the ratio is above 0.5, the precursor is excessive, and the powder will be wetted by the liquid into a slurry. After drying, the particles are prone to sticking together and clumping, requiring an additional crushing and sieving process. Moreover, the introduction of excessive alkali metals or alkaline earth metals will change the final chemical composition of the glass. Sodium methoxide, sodium ethoxide, or potassium isopropoxide are chosen for alkali metal alkoxides, while magnesium ethoxide or calcium isopropoxide are chosen for alkaline earth metal alkoxides. This is because these alkoxides have good solubility in anhydrous methanol, anhydrous ethanol, or isopropanol, eliminating the need for co-solvents or surfactants when preparing solutions. Furthermore, these alkoxides gradually decompose into their corresponding oxides or carbonates above 80°C. The decomposition products are commonly used fluxing components in glass batches, without introducing elements such as phosphorus, sulfur, and chlorine that are harmful to glass quality. Anhydrous methanol, anhydrous ethanol, or isopropanol are chosen as solvents because these three alcohols have moderate boiling points (64.7°C, 78.4°C, and 82.6°C), and can completely volatilize under vacuum drying conditions of 80–180°C, without remaining on the powder surface and affecting the glass composition. The vacuum drying temperature is set at 80–180°C because the solvent evaporation rate is too slow below 80°C, and solvent residue may remain even after drying for more than 60 minutes. Above 180°C, some alkoxides decompose prematurely before the solvent has completely evaporated, resulting in uneven distribution of decomposition products on the powder surface and affecting the anchoring effect. The drying time is controlled between 10 and 60 minutes because 10 minutes is the minimum time required for the solvent to basically evaporate at 80°C, and 60 minutes is sufficient for the alkoxides to completely decompose at 180°C. Exceeding 60 minutes has no significant additional effect. The absolute pressure is controlled between 100 and 1000 Pa because this pressure range, combined with the temperature of 80–180°C, is sufficient to significantly lower the boiling points of the three solvents, achieving rapid evaporation at a lower temperature. At the same time, this vacuum level can be achieved with a common rotary vane vacuum pump, without the need for high-cost equipment such as diffusion pumps or molecular pumps.
[0026] Specifically, in step two, an ultrasonic atomizing device is used to atomize the liquid flux precursor. The ultrasonic frequency of the ultrasonic atomizing device is 20 to 100 kHz, and the average diameter of the atomized droplets is 1 to 50 μm.
[0027] In this embodiment, an ultrasonic atomizing device is used to atomize the liquid flux precursor. The ultrasonic frequency is set to 20-100kHz. The principle is that the ultrasonic transducer converts electrical energy into high-frequency mechanical vibration. When the vibration propagates through the liquid, it generates capillary waves on the liquid surface. When the vibration intensity is sufficient, the tip of the capillary wave breaks to form micro-droplets. The higher the frequency, the finer the droplets formed. At 20kHz, the average diameter of the droplets is about 50μm, and at 100kHz, it is about 1μm. The reason for not using conventional air pressure atomization or rotary atomization is that the droplet diameters produced by those methods are usually tens to hundreds of micrometers. For powders with a particle size of 10 to 500 μm, the size of the large droplets is close to or even exceeds the size of the powder particles themselves. When encapsulating, multiple particles are easily stuck together by the same droplet. However, the 1 to 50 μm droplets produced by ultrasonic atomization are smaller than most powder particles. Each droplet can only cover part of the surface of a particle. Combined with the agitation of the powder by the rotary reactor, the droplets can be deposited layer by layer and evenly on the powder surface, avoiding adhesion caused by local liquid accumulation. At the same time, the 1 to 50 μm droplet size is also smaller than or close to the aggregate size of the pores in the surface activation layer formed in step one, and can penetrate into the interior of the pores through capillary action instead of just staying on the outer surface of the particles.
[0028] Specifically, in step one, while applying the dual-frequency composite radio frequency power supply, an axial magnetic field is also applied to the silicon-containing raw material powder, with a magnetic field strength of 0.01 to 0.5T.
[0029] In this embodiment, while applying the dual-frequency composite radio frequency power supply, an axial magnetic field with a strength of 0.01 to 0.5 T is also applied to the silicon-containing raw material powder. The direction of the applied magnetic field is parallel to the axial direction of the radio frequency electric field. The working principle is that the charged particles in the plasma are subjected to a Lorentz force perpendicular to the direction of motion while moving along the axial direction, which forces the particles to move in a spiral motion. This is equivalent to extending the residence time and path length of the particles in the reactor. In this way, each particle has more opportunities to collide and ionize with other particles before colliding with the powder, thereby improving the ionization density and uniformity of the plasma. At the same time, the spiral motion also makes the distribution of particles in the axial and radial directions more uniform, avoiding the difference in treatment effect between the center and the edge areas of the reactor. The magnetic field strength is controlled between 0.01 and 0.5 T because below 0.01 T, the Lorentz force on the particles is too small, and the radius of gyration is much larger than the reactor size, so the constraint effect is almost unobservable. Above 0.5 T, the particles are over-constrained, and the radius of gyration is too small, which restricts the particles from reaching the powder near the reactor wall, resulting in insufficient treatment of the powder near the wall. In addition, a magnetic field below 0.5 T can be generated by permanent magnets or ordinary electromagnetic coils, without the need for superconducting magnets, resulting in lower equipment costs and operating expenses.
[0030] Specifically, in step three, the working gas of the plasma activation gas flow is one or more of the following mixed gases: argon, oxygen, hydrogen, and water vapor; the external plasma generator is one of the following: a dielectric barrier discharge generator, a microwave plasma generator, or a radio frequency inductively coupled plasma generator; the long-lived active species include at least one of the following: metastable inert gas atoms, oxygen free radicals, hydrogen free radicals, and OH free radicals; and the injection flow rate of the plasma activation gas flow is 50–1000 mL / min.
[0031] In this embodiment, the working gas for plasma activation gas flow is selected from one or more of argon, oxygen, hydrogen, and water vapor because these gases, after ionization, produce different types of long-lived active species. Pure argon gas, after ionization, mainly produces metastable argon atoms with an excitation energy of approximately 11.5 eV and a lifetime of several seconds, which is sufficient to maintain activity during the process of gas flow from the external generator to the melting furnace. After entering the molten glass, the metastable atoms transfer energy through Penning collisions with the melt particles, accelerating particle motion without changing the chemical composition of the melt. The working gas containing oxygen or water vapor, after ionization, produces oxygen atom radicals or OH radicals. These radicals are highly chemically active and can directly attack the Si-O bonds in the silicon-oxygen network, reducing the activation energy required for bond breaking. The working gas containing hydrogen gas, after ionization, produces hydrogen atom radicals, which can also attack Si-O bonds and participate in bond breaking reactions. The external plasma generator is selected from three types: dielectric barrier discharge, microwave discharge, or radio frequency inductively coupled discharge. This is because all three are electrodeless discharges; the working gas is ionized in the discharge zone and then transported to the melting furnace through pipes. The generator's electrodes do not contact the high-temperature molten glass, avoiding contamination of the molten glass by the electrode materials. Furthermore, all three types of generators can operate under atmospheric or near-atmospheric pressure, and the generated gas flow pressure is sufficient to overcome the resistance of the pipes and the area below the molten pool surface. The gas flow rate is set to 50 to 1000 mL / min because below 50 mL / min, the absolute number of active species is too small and they are quickly consumed after entering the molten glass, resulting in a negligible promoting effect on the melting process. Above 1000 mL / min, a large amount of cold gas continuously injected into the melt will carry away too much heat, causing a significant drop in temperature near the injection point. Simultaneously, excessive gas flow will cause the melt to tumble violently, entraining a large amount of gas into the molten glass, forming new bubbles, and prolonging the refining time.
[0032] Specifically, in step three, the plasma activation gas flow is injected from the side wall or bottom of the glass melting furnace through a high-temperature resistant corundum tube or a platinum-rhodium alloy tube, with the injection point located 50 to 300 mm below the surface of the molten pool; the plasma activation gas flow is injected in a pulsed manner, with a pulse width of 1 to 60 seconds and a pulse interval of 10 to 300 seconds.
[0033] In this embodiment, the plasma-activated gas flow is injected from the side wall or bottom of the glass melting furnace through a high-temperature resistant corundum tube or a platinum-rhodium alloy tube. The injection point is located 50-300 mm below the surface of the molten pool. The reason for choosing to inject below the surface is that if the long-lived active species in the gas flow were introduced from above the surface, they would need to pass through the high-temperature furnace gas space before reaching the surface of the molten glass. The active species would be largely deactivated due to mutual collisions or high-temperature quenching. Even if they reached the surface, they could only act on a thin surface layer and would be difficult to penetrate into the interior of the melt. However, by inserting the injection tube directly 50-300 mm below the surface, the active species in the molten glass come into direct contact with the melt particles after the gas flow enters the melt. At the same time, the rising bubbles can also play a stirring role as they pass through the melt. The minimum depth of 50mm was chosen because if the inlet of the injection tube is too close to the liquid surface, the gas flow can easily break through the surface and escape, resulting in too short a residence time of bubbles in the melt. The maximum depth of 300mm was chosen because if the inlet is too deep, the static pressure of the melt increases, requiring a higher injection pressure to force the gas flow in. Furthermore, if the inlet is near the bottom of the furnace, it may touch the refractory material at the bottom or cause the bottom temperature to be too low. Corundum tubes or platinum-rhodium alloy tubes were chosen for the injection tubes because these two materials have good chemical stability in glass melts at 1200–1650℃. Corundum tubes are mainly composed of alumina, which does not react with most molten glass. While platinum-rhodium alloy tubes are more expensive, they offer better corrosion resistance and do not contaminate the molten glass. In pulsed injection, the pulse width is set to 1–60 seconds because if the pulse width is less than 1 second, the solenoid valve cannot complete its full opening and closing action in time, resulting in unstable gas flow. If the pulse width is greater than 60 seconds, it approaches continuous injection, failing to achieve the intermittent regulation effect of pulses. The pulse interval is set to 10–300 seconds because if the interval is less than 10 seconds, the interval between gas flow pulses is too short, and the melt does not have enough time to recover its calm state. If the interval is greater than 300 seconds, the waiting time between two pulses is too long, and the promoting effect of active species on melting cannot be sustained, resulting in insufficient total mass of active material injected per unit time. The advantage of pulsed injection over continuous injection is that the gas flow does not continuously enter the melt, but rather agitates and chemically activates the melt once during each pulse. Then, the gas injection stops during the interval, allowing sufficient time for bubbles on the melt surface to rise and dissipate. At the same time, the melt temperature can also recover to uniformity through heat conduction from the surrounding melt during the interval, avoiding localized overcooling caused by continuous gas injection.
[0034] Specifically, in step three, the melting temperature in the furnace is 1200–1650℃, the heating rate is 5–20℃ / minute, and the total melting time is 0.5–3 hours.
[0035] In this embodiment, the melting temperature is set to 1200-1650℃ because even after plasma activation and flux anchoring treatment, the depolymerization rate of the silicon-oxygen network of silicon-containing raw material powder is still too slow when the temperature is below 1200℃, and melting cannot be completed within a reasonable time. When the temperature is above 1650℃, it exceeds the long-term service temperature limit of most glass melting furnace refractory materials (such as fused zirconia corundum bricks), which will accelerate furnace erosion. The heating rate is controlled at 5-20℃ / minute because if the rate is lower than 5℃ / minute, the heating time is too long, and the powder stays in the low temperature range (such as 600-900℃) for too long during the heating process. The alkali metal or alkaline earth metal components anchored on the particle surface may react with the silicon-containing raw materials in advance in this temperature range to form a low melting point intermediate phase. After these intermediate phases form a dense layer on the particle surface, they will hinder the transfer of heat to the particle interior. If the heating rate is higher than 20℃ / minute, the heating is too fast, and the carbon dioxide produced by the decomposition of carbonate components (such as soda ash and limestone) in the glass batch cannot be discharged in time. After the powder melts, it is trapped in the glass melt and forms bubbles. The total melting time is controlled between 0.5 and 3 hours because after the first and second steps, the powder has completed the introduction of bulk structural defects and the gradient anchoring of surface fluxing components. The main processes to be completed after entering the kiln are heating to the target temperature, generating a low-melting-point mesophase and driving the melting of the entire particle, and homogenizing the melt and removing bubbles. 0.5 hours is sufficient to complete the melting of small batches or thin-layer batches, and 3 hours is sufficient to handle industrial-grade batches of large kiln feed. After 3 hours, the melting speed can not be significantly improved, and long-term high-temperature melting will increase energy consumption and kiln wear.
[0036] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0037] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A processing method for improving glass melting efficiency using plasma pretreated powder, characterized in that, Includes the following steps: Step 1: Place the silicon-containing raw material powder in the glass batch into a rotary plasma reactor. Under vacuum or inert atmosphere, apply a dual-frequency composite radio frequency power supply. The dual-frequency composite radio frequency power supply includes a first radio frequency source and a second radio frequency source. The frequency of the first radio frequency source is 2 to 10 MHz, and the frequency of the second radio frequency source is 40 to 100 MHz. The two radio frequency sources work simultaneously to obtain a bulk phase surface interface synergistically activated powder. Step 2: The bulk-to-interface synergistic activated powder obtained in Step 1 is mixed with a liquid flux precursor and spray-coated. The liquid flux precursor is an organic solution of alkali metal alkoxide or alkaline earth metal alkoxide. During the coating process, the liquid flux precursor is atomized, and the atomized droplets are deposited on the surface of the bulk-to-interface synergistic activated powder. Then, vacuum drying is performed to obtain active component gradient anchored powder. Step 3: The active component gradient anchoring powder obtained in Step 2 is mixed with the remaining raw material powder in the glass batch and then fed into the glass melting furnace for melting. At the same time, during the entire melting process or at least the early stage of melting, plasma activation gas flow is continuously or intermittently injected into the bottom of the molten pool or the batch layer of the glass melting furnace. The plasma activation gas flow is a gas flow containing long-lived active species generated by ionizing the working gas through an external plasma generator, resulting in a uniform and clear glass melt.
2. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step one, the particle size of the silicon-containing raw material powder is 10-500 μm, and the particle size distribution span (D90-D10) / D50 ≤ 2.0; the absolute pressure of the vacuum or inert atmosphere is 1-100 Pa, and the inert gas used is argon or helium; the inner wall of the rotary plasma reactor is equipped with a baffle plate, and the rotation speed is 1-20 rpm; the power of the first radio frequency source is 50-300 W, and the power of the second radio frequency source is 100-600 W.
3. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step one, the processing temperature is room temperature to 300℃, and the processing time is 5 to 60 minutes; the dual-frequency composite radio frequency power supply makes the ion energy distribution in the plasma exhibit a double-peak characteristic, wherein the energy of the low-energy ion peak is 1 to 5 eV, and the energy of the high-energy ion peak is 10 to 30 eV.
4. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step two, the mass ratio of the bulk phase interface synergistic activation powder to the liquid flux precursor is 1:0.1-0.5; the alkali metal alkoxide is at least one of sodium methoxide, sodium ethoxide, and potassium isopropoxide; the alkaline earth metal alkoxide is at least one of magnesium ethoxide and calcium isopropoxide; the organic solvent is at least one of anhydrous methanol, anhydrous ethanol, or isopropanol; the vacuum drying temperature is 80-180℃, the time is 10-60 minutes, and the absolute pressure is 100-1000 Pa.
5. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step two, the liquid flux precursor is atomized using an ultrasonic atomizing device. The ultrasonic frequency of the ultrasonic atomizing device is 20-100kHz, and the average diameter of the atomized droplets is 1-50μm.
6. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step one, while applying the dual-frequency composite radio frequency power supply, an axial magnetic field is also applied to the silicon-containing raw material powder, and the magnetic field strength is 0.01 to 0.5T.
7. A processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step three, the working gas of the plasma activation gas flow is one or more of the following mixed gases: argon, oxygen, hydrogen, and water vapor; the external plasma generator is one of the following: a dielectric barrier discharge generator, a microwave plasma generator, or a radio frequency inductively coupled plasma generator; the long-lived active species include at least one of the following: metastable inert gas atoms, oxygen free radicals, hydrogen free radicals, and OH free radicals; and the injection flow rate of the plasma activation gas flow is 50–1000 mL / min.
8. The processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step three, the plasma activation gas flow is injected from the side wall or bottom of the glass melting furnace through a high-temperature resistant corundum tube or a platinum-rhodium alloy tube, with the injection point located 50-300 mm below the surface of the molten pool; the plasma activation gas flow is injected in a pulsed manner, with a pulse width of 1-60 seconds and a pulse interval of 10-300 seconds.
9. A processing method for improving glass melting efficiency using plasma pretreated powder according to claim 1, characterized in that: In step three, the melting temperature in the furnace is 1200–1650°C, the heating rate is 5–20°C / minute, and the total melting time is 0.5–3 hours.